2019
DOI: 10.1002/sctm.18-0223
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Intrathecal and Intramuscular Application of Human Mesenchymal Stem Cells Partly Reduces the Activation of Necroptosis in the Spinal Cord of SOD1G93A Rats

Abstract: An increasing number of studies have demonstrated the beneficial effects of human mesenchymal stem cells (hMSC) in the treatment of amyotrophic lateral sclerosis (ALS). We compared the effect of repeated intrathecal applications of hMSC or their conditioned medium (CondM) using lumbar puncture or injection into the muscle ( quadriceps femoris ), or a combination of both applications in symptomatic SOD1 G93A rats. We further assessed the effect of the treatment on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 54 publications
2
24
0
1
Order By: Relevance
“…Although Intramuscular injections of hUCB-MSCs have no effect on survival of motor neurons in the spinal cord of SOD1 transgenic mice (Supplement Fig. S5) like previous study 21 , we could find that hUCB-MSCs have protective effect on skeletal muscle of transgenic mice 25,30,31 . However, the protective mechanisms of hUCB-MSCs in skeletal muscle of ALS disease models are largely unknown.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…Although Intramuscular injections of hUCB-MSCs have no effect on survival of motor neurons in the spinal cord of SOD1 transgenic mice (Supplement Fig. S5) like previous study 21 , we could find that hUCB-MSCs have protective effect on skeletal muscle of transgenic mice 25,30,31 . However, the protective mechanisms of hUCB-MSCs in skeletal muscle of ALS disease models are largely unknown.…”
Section: Discussionsupporting
confidence: 45%
“…In particular, in ALS, mesenchymal stem cells have also been used as therapeutic agents to ameliorate disease progression 20 . To date, many studies have shown that mesenchymal stem cells administered into the central nervous system, skeletal muscles or both exert positive effects on lifespan and motor function in disease models 5,7,21 . Although Intramuscular injections of hUCB-MSCs have no effect on survival of motor neurons in the spinal cord of SOD1 transgenic mice (Supplement Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations